(untitled) (Research, Society and Development, 2025)
The objective of this study is to present a literature review that analyzes how the low carbon/nitrogen (C/N) ratio in domestic wastewater limits microbial activity in processes such as anaerobic digestion, affecting the degradation of contaminants. The incorporation of bioplastics derived from banana peel (Musa paradisiaca) is proposed as a contribution of biodegradable organic carbon to optimize the C/N ratio and improve denitrification. Bioplastics, rich in starch and nutrients, increase treatment efficiency, valorizing agricultural waste and aligning with the circular economy, reducing environmental impact and dependence on fossil resources. In addition, bioplastics function as coagulants, flocculants and biodegradable substrates, facilitating the removal of contaminants and the production of biogas. Although their implementation improves biological treatments, it requires an adequate balance of nutrients such as nitrogen and phosphorus to maximize microbial activity. The results of this systematic review highlight the economic viability and sustainability, positioning bioplastics as a promising alternative as adjuvants in wastewater treatment processes, contributing to efficient waste management and the development of green technologies.